Improved sensitivity of direct microscopy for Mycobacterium tuberculosis in lymph nodes: comparison of fluorescent microscopy and modified bleach method ZN microscopy along with conventional ZN staining method - Aalmeen, Gul; Sharma, Sangeeta; Vishwasrao, Sneha; Bansal, Rani; Khare, Anjali (International Journal of Advances in Medicine, 2019)
Background: Extra pulmonary tuberculosis arises as a result of lymphatic spread from a primary focus. Fine needle aspiration cytology has assumed an important role in the evaluation of peripheral lymphadenopathy as a possible minimally invasive alternative to excisional biopsy. In most low-income countries; the only practically available bacteriologic method for diagnosing EPTB is direct smear microscopy for acid fast bacilli from the sample of the lesion. There are various methods of staining and concentration for improving sensitivity of direct microscopy for detection of tubercle bacilli in specimen. Methods: This prospective study was carried out in the Department of Pathology, Subharti Medical College and associated Chattrapati Shivaji Subharti Hospital, Meerut for a period of 2 years from July 2016 - August 2018 in 151 patients with clinical suspicion of TB and significant lymphadenopathy. Results: AFB positivity increased from 40.39% on conventional ZN stain to 48.34% on modified bleach method ZN stain and to 56.29% on Auramine-O fluorescent stain. Taking fluorescent microscopy (Auramine-O) as reference method the sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of conventional ZN stain and modified bleach method ZN stain were calculated as 71.8%, 100%, 100%, 73.33%, 84.10% and 85.33%,100%,100% ,84.61% ,92.05%, respectively. Conclusions: The addition of fluorescent microscopy (Auramine-O) and modified bleach method ZN microscopy along with conventional ZN staining method would be an important adjunct to improve the microscopic detection of Mycobacterium tuberculosis in ﬁne-needle aspirates of lymph nodes.